Characteristics of Immunomorphological Properties and Their Relationships in Cervical Cancer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cervical cancer is a major global health burden, particularly in developing countries. This study investigates the immunomorphological features of cervical cancer, focusing on immune cell infiltration, cytokine profiles, and histopathological characteristics. The analysis reveals correlations between immune activity and tumor progression, suggesting that immunomorphological profiling may guide prognosis and treatment strategies, especially in the context of immunotherapy.